PENGARUH PENCEMARAN LINGKUNGAN TERHADAP PENYEBARAN ASMA MENGGUNAKAN METODE MATEMATIKA OPTIMAL KONTROL - Panca Taufik Kurahman; Hendra Cipta (LPPM Universitas Bina Bangsa, 2023)
Journal This focus on problems pollution air. which one pollution air or pollution air this is very dangerous for health human. one _ diseases caused by pollution _ air is disease Asthma is very dangerous for health human. Objective study This For now form optimal control of the deployment model asthma with influence pollution. method math used _ in study This is the optimal control ie For determine control so that can cause a fulfilling process constraint physical, and at the same time minimize or maximize.